Teaching English as a Foreign Language and Smarter Learning Environments in the New Age of Digital Transformation - Zahra Sadat Roozafzai (Educational Challenges)
The fully online and electronic environments of today as the only way of teaching/learning require some reviews and appraisals of the paradigms of digital transformation, including the paradigm of smart education. Therefore, the current study investigated the paradigm change of the smart education to the smarter education, leading to the review of Teaching English as a Foreign Language (TEFL).